Goat Husbandary and Commerlization in Niranur Agrofarm - Deana Sophiya, Mohd Azmir; El’veinnice, Chin; Iman Irdina, Yusof; Muhammad Muizzuddin, Yusop; Nihel Shazana, Mohamed Gani; Hung Hui, Chung (UNIMAS Publisher, 2025)
The goat industry holds significant importance in Malaysia’s agro-food subsector as it provides essential nutrition to humans through meat and milk supplies. The population of goats in Malaysia are reported to be at around 572,000 animals, capable to supply up to 4,600 metric tons (MT) of mutton per year (Figure 7.1). However, the annual consumption of mutton in Malaysia is as high as 40,488 MT annually with an average per capita consumption of around 500 g over the past five years. It is obvious that the national production of mutton is unable to cope with the local demand. Consequently, Malaysia needs to import around 51,150 goats and 34,984 MT of mutton from other countries including Australia, New Zealand, South Africa and India to meet the demand (DVS, 2019).